THE ECONOMIC PAMPHLETEER: A Fair Deal for rural America - Ikerd, John (Journal of Agriculture, Food Systems, and Community Development, 2020)
First paragraph: A “fair deal” was the phrase used by Harry Truman in his 1949 State of the Union address to Congress. He said that “Every segment of our population and every individual has a right to expect from his government a fair deal” (Truman, n.d.). In a 1947 address to the NAACP, Truman had said, “Every man should have the right to a decent home, the right to an education, the right to adequate medical care, the right to a worthwhile job, the right to an equal share in the making of public decisions. . . . We must ensure that these rights—on equal terms—are enjoyed by every citizen” (Glass, 2018, para. 6). . . .